2010
DOI: 10.1590/s1415-43662010000700002
|View full text |Cite
|
Sign up to set email alerts
|

Características químicas de solo cultivado com soja e irrigado com água residuária da suinocultura

Abstract: RESUMONeste trabalho se avaliou a distribuição "in situ" de fósforo (P), matéria orgânica (MO), potássio (K), cálcio (Ca), magnésio (Mg), capacidade de troca catiônica (T), alumínio (Al), soma de bases (S), saturação por bases (V) e do pH, em um solo cultivado com soja irrigada com água residuária proveniente da suinocultura (ARS), com níveis de concentração de 0, 25, 50 e 75%. Constituiu-se um esquema fatorial a partir dos quatros níveis de concentração da ARS, das profundidades de 20, 40 e 60 cm com cinco re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
8
0
9
Order By: Relevance
“…Similar results were reported by Caovilla et al (2010), Medeiros et al (2011) and Homem et al (2014) in relation to the soil fertility properties. Caovilla et al (2010) found no significant changes in pH, base saturation, and concentrations of P, K + , Ca 2+ , and Mg 2+ in soil drip-irrigated with swine wastewater at different concentrations during soybean cultivation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported by Caovilla et al (2010), Medeiros et al (2011) and Homem et al (2014) in relation to the soil fertility properties. Caovilla et al (2010) found no significant changes in pH, base saturation, and concentrations of P, K + , Ca 2+ , and Mg 2+ in soil drip-irrigated with swine wastewater at different concentrations during soybean cultivation.…”
Section: Resultssupporting
confidence: 90%
“…Caovilla et al (2010) found no significant changes in pH, base saturation, and concentrations of P, K + , Ca 2+ , and Mg 2+ in soil drip-irrigated with swine wastewater at different concentrations during soybean cultivation. Medeiros et al (2011) found that the use of swine wastewater for cotton irrigation did not alter pH, soil organic matter, P, Ca, Cu, and Zn in the topsoil (0-0.2 m).…”
Section: Resultsmentioning
confidence: 70%
“…Para P, K,H+Al e Ca houve ajuste polinomial no qual os maiores valores observados foram de 65, 36,1; 54,3 e 70,64 % da dose recomendada respectivamente. Segundo Caovilla et al (2010) em estudos sobre as características químicas de solo com soja e irrigado com água residuária de suinocultura o solo não apresentou após o ciclo experimental aumentos nas suas características químicas, sendo observado apenas aumento de K e P na superfície do solo quando utilizados um sistema de irrigação por gotejamento.…”
Section: Doses De Adubação (%)unclassified
“…Residues from swine (Caovilla et al, 2010;Sampaio et al, 2010) and cattle (Ayuke et al, 2011) farming, for being rich in nutrients, can be used as biofertilizers in agriculture. In liquid form, these residues are more efficient when disposed on soil surface, supplying plants with water and nutrients (Caovilla et al, 2010;Sampaio et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In liquid form, these residues are more efficient when disposed on soil surface, supplying plants with water and nutrients (Caovilla et al, 2010;Sampaio et al, 2010). On the other hand, these residues in liquid form require more-detailed studies on their destination in the soil, because they can cause diffuse pollution, which is difficult to detect and control.…”
Section: Introductionmentioning
confidence: 99%